PELATIHAN EMPATI UNTUK PENCEGAHAN PERILAKU BULLYING PADA SISWA SEKOLAH DASAR - Syifa, Maulidia Nur; Purwantini, Lucky; Nadhirah Qintharah, Yuha (Universitas Islam 45 Bekasi, 2023)
Community service carried out at SDN 06 Bantarjaya regarding empathy training to prevent bullying behavior in elementary school students which aims to train and increase insight into empathetic behavior to be more respectful of fellow students in order to avoid bullying behavior. This program was implemented in accordance with the results of observations where at the time of observation there was still a lack of empathetic behavior between students, both between students and students with other school members. This activity was carried out from August to September 2023, using the method of presenting material about bullying and empathy, role playing, and the final activity was watching a video about bullying behavior, then students were given a piece of paper to write down what experiences they had while watching the video. The result of this activity is an increase in understanding about empathetic behavior and a change in students' empathetic behavior towards their fellow students.